2012
DOI: 10.1590/s1984-82502012000100012
|View full text |Cite
|
Sign up to set email alerts
|

Application of Comet assay to assess the effects of white bean meal on DNA of human lymphocytes

Abstract: This study was conducted to evaluate the potential induction of genotoxic effects of white bean flour using the Comet assay. The test was conducted with human lymphocytes present in whole blood immediately after collection, by incubation with white bean flour in three concentrations (3.92, 9.52 and 18.18 mg/ mL) at 37 °C for 4 h followed by preparation of slides. Samples were considered positive (above 20% damage) when the damage observed to cellular DNA was higher than the negative control. No genotoxic poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Various reports using beans have yielded congruent results. Lopes et al [ 54 ] examined the genotoxic potential of white bean flour by means of the comet assay and found no effect, a result that was related to the presence of polyphenolic compounds, including tannins, terpenes, and lectins. In addition, Azevedo et al [ 13 ] found no DNA damage with the comet and the micronucleus tests when cooked and dehydrated P. vulgaris (1–20%) were given to mice for 15 days; in contrast, they observed genoprotection against the damage induced by cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…Various reports using beans have yielded congruent results. Lopes et al [ 54 ] examined the genotoxic potential of white bean flour by means of the comet assay and found no effect, a result that was related to the presence of polyphenolic compounds, including tannins, terpenes, and lectins. In addition, Azevedo et al [ 13 ] found no DNA damage with the comet and the micronucleus tests when cooked and dehydrated P. vulgaris (1–20%) were given to mice for 15 days; in contrast, they observed genoprotection against the damage induced by cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…We used normal human lymphocyte, which commonly regarded as biological model for this aim (Natalia Bailon‐Moscoso et al, ). It is stated that the basic mechanisms of DNA damage are alike in various tissues, therefore recommending that the level of damage in lymphocytes may reflect those happening in other tissues (Silva Pereira et al, ). In this study, we used comet assay to evaluate genotoxicity of EEHP.…”
Section: Discussionmentioning
confidence: 99%
“…Viable cells transferred into normalmelting-point agarose, detergents and alkaline salts were used the cell membrane and placed horizontal electrophoresis tank. Damaged DNA of cell run to anode of electrophoresis with single and/or double strand breaks under alkaline conditions, cells transform into head and tail of comet [14,15]. If DNA single or double-strand breaks are not repaired, mutated cells, micronuclei, cell anomaly, and mutations can be formed in the cell [16] .…”
Section: Introductionmentioning
confidence: 99%